Литий и уран в бессточных озерах Западной Монголии; Химия в интересах устойчивого развития; Т. 20, № 2 - Шварцев С. Л. Степан Львович; Исупов В. П. Виталий Петрович; Владимиров А. Г. Александр Геннадьевич; Колпакова М. Н. Марина Николаевна; Содов Ариунбилэг; Шацкая С. С. Светлана Станиславовна; Мороз Е. Н. Екатеринаа Николаевна (2012, 2012)
Заглавие с экрана